Effectiveness of Vocabulary Applications in Enhancing the Performance of Students - Mae Ann C Paglingayen (ASEAN Multidisciplinary Research Journal, 2021)
Vocabulary development is continuously taught in basic and higher education which plays a major role in the learning process. To help the educators who are teaching vocabulary, this study entitled “Effectiveness of Vocabulary Applications in Enhancing the Performance of Students” was conducted. This descriptive – experimental study highlighted the use of presentation materials like English Vocabulary Quiz, IELTS Speaking Assistant, PowerWord, Wordster, and the use of traditional vocabulary techniques like EASE Method, Relay for Words, World Wheel, and Semantic Maps in teaching the 3rd year evening class of Bachelor of Arts in English Language students of Pangasinan State University – Bayambang Campus. The researcher focused on the performance level of the respondents in terms of their vocabulary development in the use of presentation materials and traditional vocabulary techniques. The findings revealed that the majority of the respondents are fond of reading books such as storybooks and novels and that most of the students belong to the English proficiency ‘Intermediate Level’. The performance of the students before and after being exposed to the use of presentation materials and the use of vocabulary techniques showed that there is a difference between the two approaches when used. The results of the study implicate that the use of presentation materials in vocabulary teaching has significantly improved the English proficiency level of the students compared to traditional vocabulary techniques